Draft Annual Plan (1971-72) Part-II Union Territory of Delhi - Planning Commission (Planning Commission, 1971)
In 1969-70, an outlay of Rs 0.69 crore was provided as the unutilized balance of the additional, outlay of Rs 1.00 crore which had beer made ayailable to this Territory in 1968-69 on the basis of additional resources. Further, an outlay of Rs,. 19,60 cnres is likely to be made available on the basis of additional resources of iis. 19,6 crores expected to beraised by this Territory through specific measures of additional taxation in the Fourth Plan period These outlay svauld be over and above tieoveral outlay of list 162.65 crores which has already been provided for the Fourth plan of this Territory .
Planning Department Delhi Administration